Entre a câmera e a câmara : estudo da trajetória de um comunicador-político - Pedro Pinto de Oliveira (2014)
The main goal of this research is to analyze the performance of a character that stands out as a new type of celebrity, who, imultaneously, is active on politics and media: the politician-communicator. The referred expression characterizes one who, after elected and during one's term as a city councilor, maintains one's job as a television or radio presenter. The object of this case study is the story of the real life character Everton Pop, who performs two duties: television presenter and Cuiabá's city councilor. The methodology draws upon the relational paradigm of communications, based on pragmatism, to create organizing concepts that defined the analytic frame of this research: the set of values, the system of relevances and typifications and the evaluation of the performance. This research selects 25 events of three key biographical moments of the chosen character: 1) the communicator close to being elected for a seat on the City Council; 2) the politician-communicator in action; 3) the politician-communicator on the course of his reelection campaign. This analysis reveals that the new media character expresses conservative political values and social biased moral judgement. Moreover, he elaborates a religious-political speech in order to palm his own political contradictions, to dodge himself from public problematic incidents. This research proves that the referred hybrid character occupies himself with alternating roles to gain the public's approval, interacting with his audience and voters through the media. Furthermore, this analysis concludes that the political-communicator is faced with the typical celebrity dilemma: he struggles to avoid being an ephemeral phenomenon. In the case of such a hybrid public figure, at the same time media and politician, his goal is to live off of the fame preserving his credibility.